Public online procurement system - Paridzira, Kennedy (Midlands Statement University, 2020)
The procurement of goods and services has been at the heart of many organizations as they procure to allow for work to run smoothly. This Chapter lays the foundation for the research that was undertaken to create a Online Public Procurement System. It spells out briefly the stimuli that triggered off this research. The target organization which is the Sanyati District will be examined, its background, organisational structure, vision, mission and method of operation in relationship to procurement will be given. The current challenges bedeviling the system are identified and objectives which meet the specified aim are crafted. Instruments and methods being employed to solve the problem at hand are described. They specify the planning, data collection procedures, design and development of the system and its implementation. The reasons behind the carrying out of this research will be given including the benefits of this research on on-going operations within the district.